طريقة الإستجابة الجسدية الكاملة: بين نظرية وتطبقية في تدريس مهارة الاستماع - Dhiauddin Dhiauddin (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2017)
AbstrakThis research reveals about Istima 'learning with Total Pisikal Response (TPR) method, studied theoretically and practically especially in istima' learning. This study uses literature study, to reveal the theoretical and practice in learning istima 'by TPR method. Istima Learning 'is the main scholar of Arabic language learning, where Arabic speaking for non Arabic speakers should begin with istima'. The learning of istima 'can be done by using various methods of learning, such as Total Psychical Response method, this method is very suitable for learning mahima istima' because the teacher can know the students 'vocabulary mastery and comprehension istima' and the training to students to do things that are governed by Teachers correctly. Besides, it can also create active learning with Student Center approach.الكلمة المفاتحية: الطريقة، الاستجابة الجسدية الكاملة، مهارة الاستماع